Preconception health interventions delivered in public health and community settings: A systematic review - Brown, Hilary K. (Can J Public Health, 2017)
OBJECTIVES: The objective of this systematic review was to assess the effects of preconception health interventions, delivered to individuals of reproductive age in public health and community settings, on reproductive, maternal, and child health outcomes. METHODS: A search of Ovid MEDLINE, CINAHL, EMBASE, PsychINFO, Scopus, Gender Studies Database, and SocINDEX from July 1999 through July 2016 was performed. We included studies that reported original data, used an interventional study design, included reproductive-aged women or men, were written in English, and were published in peer-reviewed journals. Two reviewers independently used standardized instruments for data extraction and quality assessment. A narrative synthesis was performed. SYNTHESIS: Twelve studies met the inclusion criteria. These studies included randomized controlled trials and quasi-experimental, pre-post, and time- series designs. Most studies were conducted in the United States; all but one study included only women. Interventions were mainly educational initiatives focused on nutrition, immunization, and lifestyle behaviours and were delivered in a single contact. The studies reported positive effects on health knowledge (n = 9), behaviour change (n = 4), and health outcomes (n = 1). Study quality was weak (n = 11) or moderate (n = 1), with limitations related to selection bias, blinding, data collection methods, and participant attrition. CONCLUSION: To develop a comprehensive, standardized approach to preconception health promotion and care in Canada, there is a clear need for high- quality research evaluating the effectiveness of preconception health interventions. Studies should use a health equity lens that includes all individuals of reproductive age and addresses the broad determinants of preconception health.